Experimental poisoning in cattle by Polygala klotzchii - Tokarnia, Carlos Hubinger; Döbereiner, Jürgen; Canella, Camillo F.C. (Pesquisa Agropecuaria Brasileira, 2014)
The green fresh aerial parts of Polygala klotzchii Chodat of the Polygalaceae family were administered orally to 14 young bovines. Eight of the animals died. Flowering plants were collected in Mato Grosso and plants in seed in the State of São Paulo. No difference in the toxicity of the plants from the two locations was observed. The least amount causing death in cattle was found to be around 10 grams of the plant per kilogram of body weight. Only one animal that showed symptoms after the ingestion of the plant did not die. This animals had received 7.5 g/kg of the plant and showed severe short-lasting symptoms and 24 hours after the administration of the plant had fully recovered. The animals showed the first symptoms either during the administration of the plant, which in these cases had to be interrupted, or shortly afferwards, i.e. from 1 hour and 50 minutes to 2 hours and 50 minutes after the beginning of the administration of the plant. The symptoms lasted from 8 hours and 22 minutes to 28 hours and 30 minutes. The period between the beginning of the administration of the plant and death of the animals was from 10 hours and 12 minutes to 31 hours. The clinical picture of the P. klotzchíi poisoning was quite uniform in all animals. The main symptoms were nervous in origin. The animals showed severe instability and rapidly fell to the ground, remaining in normal lying down position. Most of the animals succeeded in getting to their feet once or even several times, but always falling down again. They then made uncoordinated movements of the head. These were mainly horizontal, sometimes so violent that their heads hit the floor heavily. Later they lay on their side and the nervous symptoms became less proeminent; in some cases they showed sudden, severe, general muscular contractions from time to time. Besides the nervous symptoms, the animals had difficult, accelerated and irregular respiration with groaning expiration, severe diarrhoea, starting from between 2 hours and 30 minutes and a maximum of 11 hours and 10 minutes after the beginning of the administration of the plant. The anal muscles were relaxed. The post-mortem findings were also quite uniform and showed that the main lesions were in the digestive tract. Plant material could be identified easily in the rumen by their apical spines. The contents of the omasum were abnormally dry. The mucous membrane of the abomasum and the intestine was variably congested and sometimes had petechiae. The contents of the entire intestine was fluid. Peyer's patches in some cases were congested. The mesenteric lymphnodes were sometimes partially congested. The most important histopathological findings were necrobiosis and necrosis of the lymphatic tissue, especially in the follicles of the lymphnodes, the spleen as well as of the visceral and external lymphnodos, Peyer's patches, and even of the peribronchial lymphatic tissue. Furthermore, congestion and hemorrhages were seen in the central nervous system. Neither cumulative effects nor tolerance were seen in animals which ingested the plant repeatedly in sublethal doses. In experiments conducted with 4 bovines which received dried P. klotzchii, stored at room temperature, it was found that the plant did not loose any of its toxicity for at least one year.